2007
DOI: 10.1111/j.1440-0960.2007.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical herpes simplex infection masquerading as recalcitrant pemphigus vulgaris

Abstract: A 57-year-old woman presented with refractory genital erosive disease. One year earlier she experienced gingival fragility; direct immunofluorescence resulted in the diagnosis of cicatricial pemphigoid, and prednisone therapy led to initial improvement. Initial skin biopsy of her genital erosions demonstrated full-thickness ulceration with viral cytopathic change and a re-epithelializing subepidermal separation. Indirect immunofluorescence revealed intercellular IgG staining on monkey oesophagus at a titre of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…It is also relevant to observe that the majority of PV patients are treated with immunosuppressive therapy, which favors viral opportunistic infections 4 , often with atypical clinical presentation, as described by HALE & BYSTRYN 10 and KALAJIAN & CALLEN 11 Several cases of HSV as a trigger or as something which worsens PV have been described in literature (Table 1). It is observed that, in such cases, the complete remission of lesions has only occurred after introducing antiviral treatment, in the majority of cases, acyclovir.…”
Section: Discussionmentioning
confidence: 99%
“…It is also relevant to observe that the majority of PV patients are treated with immunosuppressive therapy, which favors viral opportunistic infections 4 , often with atypical clinical presentation, as described by HALE & BYSTRYN 10 and KALAJIAN & CALLEN 11 Several cases of HSV as a trigger or as something which worsens PV have been described in literature (Table 1). It is observed that, in such cases, the complete remission of lesions has only occurred after introducing antiviral treatment, in the majority of cases, acyclovir.…”
Section: Discussionmentioning
confidence: 99%
“…They found significant prevalence of HSV1 in lesions of pemphigus patients, especially in pemphigus foliaceus [13]. There have been several case reports of pemphigus with associated herpes virus infection mostly seen as a complication of immunosuppressive therapy as in our case [14][15][16][17][18][19][20][21] [ Table 2]. …”
Section: Discussionmentioning
confidence: 76%
“…Conversely, other studies suggested that herpesviruses could trigger PV progression [2,3,7,8,9]. In addition, other studies have suggested that herpesvirus infections represented a complication of pemphigus resulting from immunosuppressive therapies and/or a causative factor associated with treatment-resistant lesions [6,10,12,13,14,15,16,17,22,23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…The most common viral infections reported in pemphigus patients are caused by herpesviruses, particularly HSV [6,10,11,12,15,23,24,25,26,28,29,30]. HSV infections are often identified in association with recurrent/persistent PV lesions in patients already undergoing corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation